2021
DOI: 10.3390/healthcare9070844
|View full text |Cite
|
Sign up to set email alerts
|

Have We Taken Advantage of the Quarantine to Develop Healthy Habits? A Cross-Sectional Analysis of the Spanish COVID-19 Situation by Gender

Abstract: The confinement caused by the COVID-19 pandemic led to changes in people’s lifestyles, which in part provided an opportunity to develop habits at home. The aims were: (1) to verify if the psychological well-being (PWB) of people related to healthy habits, and if physical activity (PA) and diet mediated this relationship; (2) to test if there were differences in this model of relationships between women and men; (3) to analyze if there were differences in healthy habits, PA, diet, and PWB depending on gender; (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 79 publications
1
7
0
Order By: Relevance
“…Since this is a convenience sampling and a cross-sectional, the generalizability of the results and the causality of the relations cannot be assured. Although they are not longitudinal relations, the results are in line with previous studies ( Corbí et al, 2021 ; Del Líbano et al, 2021 ; Sousa et al., 2021 ). Therefore, it would be necessary to analyze these relations longitudinally to provide more evidence for the results obtained in this study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Since this is a convenience sampling and a cross-sectional, the generalizability of the results and the causality of the relations cannot be assured. Although they are not longitudinal relations, the results are in line with previous studies ( Corbí et al, 2021 ; Del Líbano et al, 2021 ; Sousa et al., 2021 ). Therefore, it would be necessary to analyze these relations longitudinally to provide more evidence for the results obtained in this study.…”
Section: Discussionsupporting
confidence: 92%
“…As in previous studies, the importance of healthy lifestyle habits for increasing psychological well-being and decreasing psychological distress is evident ( Bożek et al, 2020 ; Tada, 2017 ; Wittmann et al, 2010 ). Its mediating role during COVID-19 confinement between different predictors and psychological well-being or distress is also evidenced ( Corbí et al, 2021 ; Del Líbano et al, 2021 ; Sousa et al, 2021 ). In this work, the effects of psychosocial dysfunction during COVID-19 on well-being and distress appear to be mediated by healthy habits.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Some studies give evidence of women’s greater tendency to have deviated from their own dietary customs during the pandemic such as women in Italy who strayed from their Mediterranean diet [ 40 ] and women in Pakistan who trended away from their normally nutritious and diverse diet [ 41 ]. On the other hand, other studies such as one based in Spain [ 44 ], found that home confinement led to women developing better, not worse, dietary habits than men. Likewise, an Australian study found that it was men whose dietary habits became unhealthier during the pandemic, including their increased consumption of alcohol [ 45 ].…”
Section: Introductionmentioning
confidence: 95%
“…The psychological well-being (PWB) of students is the best predictor of their optimism for online learning during the pandemic (Coninck et al, 2019). Furthermore, the transition to online learning has created gender inequalities, with females experiencing lower levels of PWB due to the impact of restrictions on social relationships and limitations on movements on social determinants (Corb et al, 2021).…”
Section: Introductionmentioning
confidence: 99%